2008
DOI: 10.2460/ajvr.69.7.861
|View full text |Cite
|
Sign up to set email alerts
|

Effects of triamcinolone acetonide, sodium hyaluronate, amikacin sulfate, and mepivacaine hydrochloride, alone and in combination, on morphology and matrix composition of lipopolysaccharide-challenged and unchallenged equine articular cartilage explants

Abstract: Treatment with TA or HA supported chondrocyte morphology in culture and protected chondrocytes from toxic effects exerted by LPS, AS, and MC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
2
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 23 publications
1
48
2
3
Order By: Relevance
“…In cartilage treated with triamcinolone acetonide and mepivacaine, chondrocyte viability was intermediate between the mepivacaine-only and triamcinolone acetonide-only groups. The investigators concluded that triamcinolone acetonide attenuated the chondrotoxicity of mepivacaine [5]. In contrast, a study using a bovine cartilage found that, although the methylprednisolone showed time-and dose-dependent chondrotoxic effects, the combination of lidocaine and methylprednisolone showed a synergistic chondrocidal effect; there was no single-treatment lidocaine group for direct comparison to methylprednisolone [41].…”
Section: Discussionmentioning
confidence: 85%
“…In cartilage treated with triamcinolone acetonide and mepivacaine, chondrocyte viability was intermediate between the mepivacaine-only and triamcinolone acetonide-only groups. The investigators concluded that triamcinolone acetonide attenuated the chondrotoxicity of mepivacaine [5]. In contrast, a study using a bovine cartilage found that, although the methylprednisolone showed time-and dose-dependent chondrotoxic effects, the combination of lidocaine and methylprednisolone showed a synergistic chondrocidal effect; there was no single-treatment lidocaine group for direct comparison to methylprednisolone [41].…”
Section: Discussionmentioning
confidence: 85%
“…They suggested that mepivacaine would be a safer alternative to lidocaine or bupivacaine. Bolt et al 19 assessed the effect of mepivacaine hydrochloride on articular cartilage explants obtained from four patella-femoral joints of two adult horses. On histological assessment, they found increased number of pyknotic nuclei and empty lacunae …”
Section: 2mentioning
confidence: 99%
“…Verschiedene In vitro-Studien an equinen Chondrozyten bestätigen den chondroprotektiven Effekt von TA (Bolt et al 2008, Busschers et al 2010, Garvican et al 2010 werden (Bolt et al 2008). An mit IL-1 und anderen Entzün-dungsmediatoren behandelten Knorpelexplantaten wurde auch der hemmende Einfluss von TA auf den durch MMPs induzierten Knorpelkatabolismus deutlich.…”
Section: Triamcinolonacetonidunclassified
“…Anhand von einem In vivoVersuch, durchgeführt mit Kaninchen stellte sich zusätzlich heraus, dass HA, intraartikulär appliziert, in gleicher Menge und mit gleichem Molekulargewicht (getestet mit verschiedenen Produkten 9/12x10 5 Da) keinen einheitlichen Die intraartikuläre Corticosteroidtherapie wird häufig mit HA kombiniert. In-vitro konnte die negative Wirkung von LPS und IL-1 auf Chondrozyten sowohl durch Zugabe von HA, als auch durch TA und die Kombination der beiden Wirkstoffe gemindert werden (Bolt et al 2008, Schaefer et al 2009). Eine randomisierte klinische Studie aus der Humanmedizin kam zu dem Ergebnis, dass Patienten die die Kombination von TA und HA erhielten weniger unter Gelenkschmerz litten, als Patienten die nur mit HA behandelt wurden (Ozturk et al 2006).…”
Section: Hyaluronsäureunclassified
See 1 more Smart Citation